Segmenting the Universe into dynamically coherent basins. Issue 3 (24th February 2020) - Dupuy, Alexandra; Courtois, Hélène M; Libeskind, Noam I; Guinet, Daniel
ABSTRACT: This paper explores in depth a watershed concept to partition the Universe, introduced in a previous Letter and applied to the Cosmicflows-3 observational data set. We present a series of tests conducted with cosmological dark matter simulations. In particular, we are interested in quantifying the evolution with redshift of large-scale structures when defined as segmented basins of attraction. This new dynamical definition in the field of measuring standard rulers demonstrates robustness since all basins show a density contrast δ above 1 (mean Universe density) independently of the simulation spatial resolution or the redshift. Another major finding is that density profiles of the basins show universality in slope. Consequently, there is a unique definition of what is a gravitational watershed at a large scale, which can be further used as a probe for cosmology studies.